Price-based low-carbon demand response considering the conduction of carbon emission costs in smart grids - Yang, Chao; He, Binghao; Liao, Huanxin; Ruan, Jiaqi; Zhao, Junhua (Frontiers in Energy Research, 2022)
The rapid development of the Industrial Internet-of-Things extends demand response research to the field of low-carbon emission in smart grids. This paper puts forward the concept of low-carbon demand response (LCDR) in the electricity market and proposes the price-based LCDR mechanism and its model. Firstly, the carbon cost conduction from generation side to demand side is analysed, and then the conduction function is deduced quantifiedly. Secondly, the mechanism and model of price-based LCDR are proposed by considering three DR signals, such as the electricity price, the carbon price and the carbon emission intensity of the demand side, based on the traditional price-based demand response mechanism. Then, the proposed LCDR mechanism is applied to the environmental economic dispatch optimization problem. Finally, case studies on the modified IEEE 39-bus system verify that the LCDR mechanism can reduce carbon emissions while maintaining the function of the traditional price-based demand response. Meanwhile, the applicability of LCDR is illustrated based on the carbon emission sensitivity to LCDR model parameters. The proposed mechanism can be important guidance for participants in the electricity market to reduce electricity carbon emissions.